Perceptions of Students and Teachers of the University of Montenegro on Academic Integrity - Sanja Čalović Nenezić; Milena Krtolica; Milica Jelić; Suzana Šekarić (Center for Educational Policy Studies Journal)
At the University of Montenegro, increasing emphasis has recently been placed on academic integrity. Academic integrity is based on the principles of honesty, objectivity, openness, freedom in teaching and research, and responsibility to academia and society/the community. One of the basic principles of academic integrity is honesty. The present study is based on examining the perception of students and teachers of the University of Montenegro concerning different segments of academic honesty. The aim of the research was to examine ethical behaviour related to respect for someone else’s work (using and referring to literature) and copying as well as using illicit means in exams. The research was conducted using quantitative research on a sample of 200 students and 50 teachers at the University of Montenegro. For this purpose, the authors used a Likert-type assessment scale. The findings suggest that the respondents understand the importance of academic integrity, that is, honesty as its principle, but that they do not recognise all of the segments that it covers in the same way. For example, different answers were received regarding the claim that students copy papers without paraphrasing, and despite the observed negative attitude towards the disciplinary procedure in both groups, teachers seem to lead in this attitude.